Evaluating the Causes of Deductions for Inpatient Bills Covered by Social Security Insurance in Rofeideh Hospital, Tehran City, Iran, in 2021 - Seyedeh Mahboobeh Hosseini Zare; Jafar Babapour; Mehdi Basakha; Seyed Mahdi Mohsenzadeh4; Parvaneh Esfahani; Seyedeh Masoumeh Hosseini Zare; Najmeh Ashouri; Bijan Khorasani (University of Social Welfare and Rehabilitation Sciences, 2024)
Objective Insurance deductions are among the most important causes of hospital resource waste. Insurance deductions cause financial problems for hospitals and create tension between insurance organizations and hospitals. This study, done by the University of Social Welfare and Rehabilitation Sciences, investigates the reasons for deductions of inpatient bills covered by Social Security Insurance in Rofeideh Rehabilitation Hospital Materials & Methods The study was conducted cross-sectionally on 776 cases admitted to Rofeidah Rehabilitation Hospital in 2021. All invoices for inpatient services sent to Social Security Insurance were reviewed using the census method. To collect data, invoices sent to Social Security, inpatient records and checklists, and a 31-question questionnaire of Mohammadkhani et al. were used. The collected data were analyzed by descriptive (frequency and percentage) and analytical statistics (the Spearman correlation coefficient) in SPSS software, version 23. Results According to the findings, the highest frequency of inpatient prescriptions was related to November 2021 (7.48%). The most frequent deductions of inpatients' bills were related to medicine and consumables to the amount of 310815448 Rails and surgeon's fees in 187728448 Rails. Also, the most common reasons were requesting a surcharge and wrong coding. In this study, there was a significant relationship between the documentation of nurses and doctors and the amount of deductions (P<0.0001). Conclusion Multiple causes affect the reduction of insurance deductions. By teaching insurance rules and the book on the relative value of health services to medical and nursing staff groups, electronic documents to Social Security Insurance and creating warning mechanisms in it, continuous interaction with Social Security Insurance to justify the managers of the organization regarding the way of providing services to rehabilitation patients and the reason for the prolonged hospitalization time of such patients could be the potential solutions for preventing patients records deductions and help hospitals achieve financial goals.